Phylogeny and taxonomy of powdery mildew on Viburnum species. (3rd May 2020) - Bradshaw, Michael; Braun, Uwe; Wang, Serena; Liu, Shuyan; Feng, Jing; Shin, Hyeon-Dong; Choi, Young-Joon; Takamatsu, Susumu; Bulgakov, Timur S.; Tobin, Patrick C.
ABSTRACT: The phylogeny and taxonomy of powdery mildew on Viburnum species is evaluated and discussed. Morphological and phylogenetic analyses revealed two new species and demonstrated that Erysiphe hedwigii and E. viburni should be reduced to synonymy and are referred to herein as E. viburni . The two new species, E. viburniphila and E. pseudoviburni, previously hidden under E. viburni (including E. hedwigii ), is described on the basis of European, North American, and East Asian powdery mildew collections on Viburnum edule, V. tinus, V. odoratissimum var. awabuki, and V. sieboldii . The sexual morph of E. viburniphila is similar to that of E. viburni ; however, morphological differences exist in their asexual morphs. Analyses of sequences from the internal transcribed spacer (ITS) and 28S genomic regions of Erysiphe species obtained on Viburnum species (and other closely allied Eryisphe species) throughout the world reveled that E. viburniphila and E. pseudoviburni are in two different monophyletic groups that are separate from all other Erysiphe species. Erysiphe hedwigii and E. viburni on Viburnum species have often been recognized as separate species based on morphological differences in the size of their chasmothecia and the number of chasmothecial appendages. Taxonomic conclusions based on these morphological distinctions within these species are unreliable (these characters are rather variable and often have overlapping ranges). The present phylogenetic analyses suggest that E. hedwigii has to be reduced to synonymy with E. viburni . To fix the application of the species names E. hedwigii and E. viburni, epitypes have been designated for these taxa with ex-epitype sequences. Additionally, the Asian species E. miranda is phylogenetically confirmed as a species of its own, described in detail and discussed.